Plexiform intra-spinal neurofibromatosis in a young male with lower limb radiculopathy: A case report and review of literature - Ashish Shankar Naik; Chandhan Murugan; K S Sri Vijay Anand; Shanmuganathan Rajasekaran (Indian Spine Journal, 2023)
Neurofibromatosis type 1 (NF-1) with extensive intraspinal involvement seldom presents with isolated radiculopathy. We report the case of a young male with NF-1 having dumbbell tumors along the entire extent of the spine presenting with isolated lower limb radiculopathy. The surgical goals for such tumors primarily involve symptom control, rather than “cure” of a specific lesion, with intervention typically reserved for lesions that significantly compress vital structures symptomatically. Clinical examination and magnetic resonance imaging clinched the symptomatic level in our patient to be L4–L5 and L5–S1, who significantly improved following a decompression surgery.